Isolation and Identification of a Rumen Lactobacillus Bacteria and Its Degradation Potential of Gossypol in Cottonseed Meal during Solid-State Fermentation - Wei-Kang Wang (MDPI AG, 2021)
Cottonseed meal (CSM) is an important protein feed source for dairy cows. Its inclusion in ruminant diets is limited due to the presence of the highly toxic gossypol though rumen microorganisms are believed to be capable of gossypol degrading and transforming. The objective of the present study was to isolate the gossypol-degrading bacteria from the rumen contents and to assess its potential for gossypol degradation in vitro. A strain named Lactobacillus agilis WWK129 was anaerobically isolated from dairy cows after mixed rumen microorganisms were grown on a substrate with gossypol as the sole carbon source. Furthermore, the strain was applied at 5% inoculum concentration in vitro to continuously ferment CSM at 39 °C for five days, and it presented gossypol degradability as high as 83%. Meanwhile, the CSM contents of crude protein, essential amino acids increased significantly along with the increase of lactic acid yield (p < 0.01). Compared with the original CSM, the fermented CSM contents of neutral detergent fiber and acid detergent fiber was remarkably decreased after the anaerobic fermentation (p < 0.01). In brief, the Lactobacillus strain isolated from the rumen is not only of great importance for gossypol biodegradation of CSM, but it could also be used to further explore the role of rumen microorganisms in gossypol degradation by the ruminants.